Public Health and Primary Care: Competition or Collaboration - Adalsteinn D. Brown, Ross Upshur and Terrence J. Sullivan (HealthcarePapers, 2013)
In this commentary, the authors summarize and discuss some of the concerns presented in the papers herein, including issues of funding, skill sets and education. They present two key steps we could take across this country to ensure the long-term viability of public health within our healthcare system and ensure that public health and population goals are shared widely across our health systems.
Keywords: Public health, primary care, population health, system transformation